2021
DOI: 10.48550/arxiv.2107.00044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The distribution of mutual inclinations arising from the stellar quadrupole moment

Kathleen Schultz,
Christopher Spalding,
Konstantin Batygin

Abstract: A large proportion of transiting planetary systems appear to possess only a single planet as opposed to multiple transiting planets. This excess of singles is indicative of significant mutual inclinations existing within a large number of planetary systems, but the origin of these misalignments is unclear. Moreover, recent observational characterization reveals that mutual inclinations tend to increase with proximity to the host star. These trends are both consistent with the dynamical influence of a strong qu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…We note that stellar oblateness (also known as J2) can induce nodes precession of an ultra short planet. It was suggested that this precession may even result in inducing small mutual inclination between multi-planet systems ( ∼ < 40 • e.g., Becker et al 2020;Li et al 2020;Schultz et al 2021). As highlighted in Wei et al (2021), stability analysis can be done for wide variety of shortrange forces.…”
Section: Discussionmentioning
confidence: 99%
“…We note that stellar oblateness (also known as J2) can induce nodes precession of an ultra short planet. It was suggested that this precession may even result in inducing small mutual inclination between multi-planet systems ( ∼ < 40 • e.g., Becker et al 2020;Li et al 2020;Schultz et al 2021). As highlighted in Wei et al (2021), stability analysis can be done for wide variety of shortrange forces.…”
Section: Discussionmentioning
confidence: 99%